2021
DOI: 10.25248/reas.e6274.2021
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da hanseníase nas Mesorregiões do Pará, um Estado hiperendêmico do Norte do Brasil, 2004-2018

Abstract: Objetivo: Analisar a tendência da detecção da hanseníase, na população em geral, nas Mesorregiões do estado do Pará, Brasil, no período de 2004 a 2018. Métodos: Estudo ecológico exploratório utilizando o banco de dados do Sistema de Informação de Agravos de Notificação. Foram incluídos os casos de hanseníase residentes no estado de Pará. Estudadas 57.537 notificações de caso, considerando as variáveis: sexo, raça/cor da pele, idade, escolaridade, município de residência, ano da detecção da doença, classificaçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study demonstrated that leprosy is prevalent in vulnerable populations with low socioeconomic status, highlighting social inequalities, since resources aimed at health do not coincide with the interests and health needs of the population in certain regions of the country [12].…”
Section: Discussionmentioning
confidence: 87%
“…This study demonstrated that leprosy is prevalent in vulnerable populations with low socioeconomic status, highlighting social inequalities, since resources aimed at health do not coincide with the interests and health needs of the population in certain regions of the country [12].…”
Section: Discussionmentioning
confidence: 87%